PET TRACKING SYSTEM USING IoT - Kiew, Amelia Lee Ping (Universiti Malaysia Sarawak (UNIMAS), 2020)
Pet care is progressively gaining more attention. Even with the growth of wireless technology, application to pets has not been much researched. Finding a lost pet through flyers, a walk or drive around the neighborhood, posting on media, etc. would generally take a longer time to locate the lost pet especially when a certain period of time has passed. Now, with the Internet of Things, owners can look up their pets’ location on a desktop or mobile application through GPS. The “Pet Tracking System IoT” uses advanced technology that enables it to have multiple functions. It is able to perform functions like GPS tracking, location history and distance monitoring using sensors.